Code Switching Occur in Susah Sinyal Movie - Verani Natalia Ferdi; Putu Ayu Asty Senja Pratiwi; Ni Made Suwari Antari (Pusat riset dan Inovasi Nasional, 2025)
This study explores the phenomenon of code-switching as portrayed in the Susah Sinyal movie. Code-switching is the practice of alternating between two or more languages within a single conversation, commonly done by bilingual individuals for different social and communicative reasons. The objective of this research is to examine the types of code-switching using the framework of Romaine (1989) and to describe its communicative functions based on the theory of Appel and Muysken (2006). The data were obtained from the movie using documentation techniques and analyzed using a descriptive qualitative method. The analysis revealed three types of code-switching, namely intra-sentential, inter-sentential, and tag-switching. Additionally, the study identified six functions of code-switching: referential, directive, expressive, phatic, metalinguistic, and poetic. Overall, the use of code-switching in Susah Sinyal movie demonstrates how the characters strategically shift between languages to clarify meaning, convey feelings, direct actions, maintain social bonds, reflect identity, and enhance expression, reflecting the dynamic nature of bilingual communication in Indonesian popular media.